The analysis of the geomagnetic data during the installation of the first MAGDAS system at the Malaysian space agency / K. Burhanudin ...[et al.] - Burhanudin, K.; Jusoh, M.H; Latiff, Z.I.A; Zainuddin, A.; Kamaruddin, F.; Hashim, M.H (UiTM Press, 2022)
Magnetic Data Acquisition System (MAGDAS) is a system of the real-time magnetometer deploy by Kyushu University of Fukuoka, Japan as a part of the contribution to the International Heliophysical Year of United Nations[1]. The magnetometer used for real-time data acquisition is YU-8T SN-59, which is a part of the first model of the MAGDAS magnetometer. This paper discussed the characteristic of the magnetic data from the MAGDAS BTG and the possibility of the data to be used for further research study in the field of space and weather. There is 3 main magnetic field component from YU-8T magnetometer that describes the magnetic field which is Horizontal Intensity (Hcomponent), Declination (D-component) and Vertical Component (Z-component). The installation of the MAGDAS system is located at Malaysian Space Agency (MYSA), Banting (BTG), Malaysia (geographic latitude and longitude: 2.78ᴼ, 101.51ᴼ, and geomagnetic latitude and longitude: 6.86ᴼ, 174.10ᴼ). The YU-8T magnetometer measures the earth's magnetic field in horizontal intensity(H), declination(D), and field down(Z). The magnetic field data were collected, analyze, and compared with the MAGDAS LKW, USM, and the World Magnetic Model (WMM) to verify the performance of the MAGDAS BTG. The importance of the study is to identify the reliability and characteristic of the magnetic data from the MAGDAS BTG in response to the solar event and GIC formation.